A Detailed Analysis of the BR1 Locus Suggests a New Mechanism for Bolting after Winter in Sugar Beet (Beta vulgaris L.) - Tränkner, Conny; Lemnian, Ioana M.; Emrani, Nazgol; Pfeiffer, Nina; Tiwari, Surya P.; Kopisch-Obuch, Friedrich J.; Vogt, Sebastian H.; Müller, Andreas E.; Schilhabel, Markus; Jung, Christian; Grosse, Ivo (Frontiers in Plant Science, 2016)
Sugar beet (Beta vulgaris ssp. vulgaris) is a biennial, sucrose-storing plant, which is mainly cultivated as a spring crop and harvested in the vegetative stage before winter. For increasing beet yield, over-winter cultivation would be advantageous. However, bolting is induced after winter and drastically reduces yield. Thus, post-winter bolting control is essential for winter beet cultivation. To identify genetic factors controlling bolting after winter, a F2 population was previously developed by crossing the sugar beet accessions BETA 1773 with reduced bolting tendency and 93161P with complete bolting after winter. For a mapping-by-sequencing analysis, pools of 26 bolting-resistant and 297 bolting F2 plants were used. Thereby, a single continuous homozygous region of 103 kb was co-localized to the previously published BR1 QTL for post-winter bolting resistance (Pfeiffer et al., 2014). The BR1 locus was narrowed down to 11 candidate genes from which a homologue of the Arabidopsis CLEAVAGE AND POLYADENYLATION SPECIFICITY FACTOR 73-I (CPSF73-I) was identified as the most promising candidate. A 2 bp deletion within the BETA 1773 allele of BvCPSF73-Ia results in a truncated protein. However, the null allele of BvCPSF73-Ia might partially be compensated by a second BvCPSF73-Ib gene. This gene is located 954 bp upstream of BvCPSF73-Ia and could be responsible for the incomplete penetrance of the post-winter bolting resistance allele of BETA 1773. This result is an important milestone for breeding winter beets with complete bolting resistance after winter.